Gut dysbiosis associated with clinical prognosis of patients with primary biliary cholangitis - Furukawa, Masanori; Moriya, Kei; Nakayama, Jiro; Inoue, Takako; Momoda, Rie; Kawaratani, Hideto; Namisaki, Tadashi; Sato, Shinya; Douhara, Akitoshi; Kaji, Kosuke; Kitade, Mitsuteru; Shimozato, Naotaka; et al. (Hepatology research, 2020)
Aim Although some relationships between gut microbiota and liver diseases have been reported, it remains uncertain whether changes in gut microbiota owing to differences in race, food and living environment have similar effects. Response to ursodeoxycholic acid (UDCA) may predict the long‐term prognosis of patients with primary biliary cholangitis (PBC); however, little is known about the significance of the gut microbiome in patients with PBC. We elucidated the relationships among clinical profiles, biochemical response to UDCA and gut microbiome composition in patients with PBC. Methods Fecal samples from 76 patients with PBC treated at our hospital were collected; patients whose UDCA intake period was <1 year were excluded. The microbiome structures of patients were determined using 16S ribosomal RNA gene sequencing and were statistically compared with those of healthy subjects. The structures of patients in the UDCA responder (n = 43) and non‐responder (n = 30) groups were compared according to the Nara criteria (reduction rate of gamma‐glutamyl transpeptidase, ≥69%, after 1 year). Results Compared with healthy subjects, bacterial diversity was lower in patients with PBC, with a decreased abundance of the order Clostridiales and increased abundance of Lactobacillales. The UDCA non‐responder group had a significantly lower population of the genus Faecalibacterium, known as butyrate‐producing beneficial bacteria (P < 0.05), although no significant differences in gender, body mass index, medicated drugs or other serological data were indicated between these two groups. Conclusions Gut dysbiosis with loss of beneficial Clostridiales commensals was observed in patients with PBC. Decrease in Faecalibacterium abundance might predict the long‐term prognosis of patients with PBC.